Customer engagement in social media - Santini, Fernando de Oliveira (2022)
Santini, F. D. O., Ladeira, W. J., Pinto, D. C., Herter, M. M., Sampaio, C. H., & Babin, B. J. (2020). Customer engagement in social media: a framework and meta-analysis. Journal Of The Academy Of Marketing Science. [Advanced online publication on 27 May 2020]. Doi: https://doi.org/10.1007/s11747-020-00731-5